NATURE DEPICTION AND AUTHOR’S MASTERY IN THE TALE GENRE - Latofat Husanovna Abdullayeva (Bright Mind Publishing, 2026)
In the tale genre, nature depiction plays a crucial role in creating the setting, reflecting the psychological state of characters, developing the plot, and enhancing artistic aesthetics. Natural phenomena also help determine the pace of the narrative, create dramatic effect, and provide symbolic meaning. Therefore, nature depiction is an integral artistic element of the tale genre.
Keywords: Tale, nature depiction, plot, character psychology, artistic aesthetics.